Purificação, caracterização e imobilização de lacases de basidiomicetos e seu uso na degradação simultânea de rifampicina e isoniazida - Riedi, Halanna de Paula (2019)
Rifampicin and isoniazid are antibiotics used for the treatment of tuberculosis. Around 30% of pharmaceuticals are expelled from the body in its unchanged form and when are not properly treated in the sewage treatment plants can be responsible for the proliferation of resistant bacteria. Different techniques have been proposed for the treatment of pharmaceuticals in the environment, including biological methods with the use of fungal enzymes. Between them the application of immobilized laccases by cross-linked enzyme aggregates (CLEAs) for the biodegradation of micropolutants is a promising alternative. In this study were evaluated the purification, characterization and immobilization of laccases from basidiomycetes by CLEAs technique for subsequent application of the enzymes as biodegradant agents of rifampicin and isoniazid. The paper was divided into six steps, being these: (1) laccase production by basidiomycetes, resulting at maximum activity for Trametes sp of 9412,91 U/L and for Pleurotus ostreatus 12296,03 U/L; (2) enzyme immobilization by CLEAs obtaining 16,42% of enzimatic immobilization; (3) purification of laccases obtained by precipitaion with (NH4)2SO4, dialysis and gel chromatography with specific activity of 7,77 U/mg for Trametes sp. and 6,3 U/mg for P. ostreatus; (4) characterization of the enzymes with respect to the effects of pH, temperature and determination of the kinetic constants, where it was possible to observe that for both laccases the optimum pH was 4,0 and stability between 3,0 and 5,0 and optimum temperature of 60 °C and thermostability between 20°C to 50 °C for 1 hour. For the immobilized enzyme were observed stability increase for all pHs and in temperature between 20 to 60°C. Free lacases of Trametes sp. obtained Km of 1 mM and Vmax of 454 µmol/min, while CLEAs obtained 3,94 and 140,84, respectively. For P. ostreatus free enzyme the Km was 2,1 mM and Vmax 1000 µmol/min, while immobilized obtained Km of 2,57 mM and Vmax of 70,42 µmol/min; (5) pharmaceuticals simultaneous biodegradation resulted in higher treatment performance of isoniazid using immobilized enzymes with 71% removal for Trametes sp. while free laccase displayed 32%. P. ostreatus had similar results, with 68,8% for CLEAs and 26,4% with free enzymes. Rifampicin didn’t have significant difference between treatments, with both removing more than 93%; (6) antimicrobial analysis after enzymatic treatment revealed that rifampicin still had antimicrobial properties, inhibiting growth in low concentrations of 0,22 mg/L.